Degradation of Paraquat in Gramoxone Pesticide with Addition of ZnO - Febrina Arfi; Safni Safni; Zaimi Abdullah (Universitas Jenderal Soedirman, 2017)
Paraquat is the most toxic herbicide, the main agricultural crops and plantations that use them are cloves, cocoa, oil palm, rubber, coffee, and pepper. Therefore, it is necessary to study to degrade paraquat compounds by photolysis method with using ZnO. Photolysis is a process of UV irradiation with a wavelength of 200-400 nm. In this study Photolysis method used UV light with λ = 365 nm. Degradation of paraquat compound was done with the influence of variation of time without the addition ZnO, the influence of ZnO additional variations, and the effect of combination between variations of time and optimization of ZnO addition. The result of the study shows that photolysis degradation product without the addition of ZnO for 120 minutes has been degraded by 12.56%. While the optimum addition of 0.1 grams ZnO increased the percentage of degradation which is about 57.64%. This is proved that the addition of ZnO with photolysis method can degrade more paraquat compounds.